Potential for reduced methane and carbon dioxide emissions from livestock and pasture management in the tropics - Thornton, Philip K.; Herrero, Mario (National Academy of Sciences, 2010)
We estimate the potential reductions in methane and carbon dioxide emissions from several livestock and pasture management options in the mixed and rangeland-based production systems in the tropics. The impacts of adoption of improved pastures, intensifying ruminant diets, changes in land-use practices, and changing breeds of large ruminants on the production of methane and carbon dioxide are calculated for two levels of adoption: complete adoption, to estimate the upper limit to reductions in these greenhouse gases (GHGs), and optimistic but plausible adoption rates taken from the literature, where these exist. Results are expressed both in GHG per ton of livestock product and in Gt CO2-eq. We estimate that the maximum mitigation potential of these options in the land-based livestock systems in the tropics amounts to approximately 7% of the global agricultural mitigation potential to 2030. Using historical adoption rates from the literature, the plausible mitigation potential of these options could contribute approximately 4% of global agricultural GHG mitigation. This could be worth on the order of $1.3 billion per year at a price of $20 per t CO2-eq. The household-level and sociocultural impacts of some of these options warrant further study, however, because livestock have multiple roles in tropical systems that often go far beyond their productive utility.